Understanding Lifetime Homeless Duration: Investigating Wave 1 Findings from the Journeys Home Project - Moschion, J; Tseng, Y; Scutella, R; Johnson, G; Wooden, M (My University, 2013)
The variation in the amount of time people remain homeless has important policy implications with respect to reducing long‑term homelessness and designing more effective early intervention approaches. This paper examines the factors that influence lifetime homeless duration in Australia using data from the first wave of Journeys Home, a new national survey of individuals exposed to high levels of housing insecurity that employs more rigorous sampling methods than previously used. Those at increased risk of long durations of homelessness over their lifetimes include people who had less family support in childhood, shorter work histories and lower education levels. We also find evidence supporting the idea that people who first experience homelessness at a young age are more likely to experience persistent homelessness.
Keywords: Social Capital -- Resilience and Adversity; Housing; Income & Finance -- Poverty and disadvantage; Income, wealth and finances; Income & Finance; Housing; Social Capital; Resilience and Adversity; Poverty and disadvantage; Income, wealth and finances